Assessing soil fertility status and land suitability for patchouli plants (Pogostemon cablin Benth.) in Lamala District, Banggai Regency - Yulinda Karundeng; Hertasning Yatim; Hidayat Arismunandar Katili; Lina Lathifah Nurazizah (Faculty of Agriculture, Tompotika Luwuk University, 2021)
Besides influenced by genotype, the quality and quantity of patchouli essential oil were controlled by soil as a growing medium. The development of patchouli plantation in Lamala District is still hampered by negative stigma from the community. It is believed, the strong absorption rate from patchouli could lead to soil nutrient deficiency. The purpose of this study was to determine soil fertility status and evaluate its suitability for patchouli plant in 3 land units (e.g., uncultivated, cultivated with fertilization, and cultivated without fertilization). The method used is an Exploratory-Descriptive Survey. The determination of soil properties was based on physical properties such as texture, and chemical properties such as pH, organic-C and nitrogen, P2O5 and K2O, base cations and cation exchange capacity/CEC, and Fe. The data then matched to Soil Fertility and Land Suitability Criteria for the patchouli plant. The result showed that the chemical properties in 3 land units had slightly acidic, high CEC, medium base saturation, moderate P2O5 content, and moderate organic-C content. Meanwhile, the K2O content of the land without patchouli was very low and the patchouli with and without fertilizer was low. Soil fertility status in 3 land units was classified as marginally suitable (S3-rc,na), this is due to the limiting factors; soil texture (rc) and P2O5 (na).